Structural-functional model of personality socialization schoolboy in the transition to 12-year education - Н. Жиєнбаева (Київський національний університет імені Тараса Шевченка, 2015)
This article presents the results of psychological research, the aim of which was to study the age characteristics of adolescent development. This study was conducted during the transition to 12-year course of study. Conducting psychological research has revealed the necessary psychological and pedagogical conditions for personal development and socialization of the personality of students in the new learning environments.

У цій статті наводяться результати психологічного дослідження, метою якого було вивчення вікових особливостей розвитку підлітків. Дане дослідження проводилося на етапі переходу на 12-річну форму навчання. Проведене психологічне дослідження виявило необхідні психолого-педагогічні умови для особистісного розвитку та соціалізації особистості школярів в нових умовах навчання.
Структурно-функціональна модель соціалізації особистості школяра в умовах переходу на 12-річне навчання
Keywords: школьники; направленность личности; характер; система управления; концепция образования; модель; students; orientation of the personality; character; control system; the concept of education model.; students; orientation of the personality; character; control system; the concept of education; model